Spinophilin Is Indispensable for the α2B Adrenergic Receptor-Elicited Hypertensive Response. - Pulin Che; Yunjia Chen; Roujian Lu; Ning Peng; Mary Gannon; J Michael Wyss; Kai Jiao; Qin Wang (PLoS ONE, 2015)
The α2 adrenergic receptor (AR) subtypes are important for blood pressure control. When activated, the α2A subtype elicits a hypotensive response whereas the α2B subtype mediates a hypertensive effect that counteracts the hypotensive response by the α2A subtype. We have previously shown that spinophilin attenuates the α2AAR-dependent hypotensive response; in spinophilin null mice, this response is highly potentiated. In this study, we demonstrate that spinophilin impedes arrestin-dependent phosphorylation and desensitization of the α2BAR subtype by competing against arrestin binding to this receptor subtype. The Del301-303 α2BAR, a human variation that shows impaired phosphorylation and desensitization and is linked to hypertension in certain populations, exhibits preferential interaction with spinophilin over arrestin. Furthermore, Del301-303 α2BAR-induced ERK signaling is quickly desensitized in cells without spinophilin expression, showing a profile similar to that induced by the wild type receptor in these cells. Together, these data suggest a critical role of spinophilin in sustaining α2BAR signaling. Consistent with this notion, our in vivo study reveals that the α2BAR-elicited hypertensive response is diminished in spinophilin deficient mice. In arrestin 3 deficient mice, where the receptor has a stronger binding to spinophilin, the same hypertensive response is enhanced. These data suggest that interaction with spinophilin is indispensable for the α2BAR to elicit the hypertensive response. This is opposite of the negative role of spinophilin in regulating α2AAR-mediated hypotensive response, suggesting that spinophilin regulation of these closely related receptor subtypes can result in distinct functional outcomes in vivo. Thus, spinophilin may represent a useful therapeutic target for treatment of hypertension.